UJI KESESUAIAN CT NUMBER PADA PESAWAT CT SCAN MULTI SLICE DI UNIT RADIOLOGI RUMAH SAKIT ISLAM YOGYAKARTA PDHI - Ali Roo'in Mas'uul; Heri Sutanto (Youngster Physics Journal, 2014)
CT number is the value of x rays attenuation coefficient determined by the average energy of the x-rays and atomic number absorber and expressed by the attenuation coefficient. function CT number in CT Scan is to assess and differentiate abnormalities in human organs. If there are inaccuracies value of CT number, it can happen misdiagnosis and treatment of patients that successive actions, so the need for periodic compliance of the test.Suitability tests were conducted to value of CT number multislice CT Scan in Radiology Unit of the PDHI Yogyakarta Islamic Hospital. Suitability test were conducted by using a water phantom, 10 mm slice thickness, 140 kV and 280 mAs, gantry tilt of 0 °, round or circular ROI with a size of 2-3 cm. Measurement samples were taken from 5 different regions which the first area in the center of the phantom images, as well as four other regions on the edge of the peripheral or phantom image. From the test have been gotten value of CT number for the water phantom at 5 different positions  2.03 ; 1.38 ; 1.60 ; 1.79 ; 1.83 HU. Five different positions has had no single value that is the result exceeds the tolerance limit of ≤ 4 HU thus all CT values for the number of water which is within the tolerance limit with a value of -4 up  to 4 HU, so it could be concluded that the results of the reading CT number on the  multislice CT Scan  in Radiology Unit of the Islamic Hospital Yogyakarta PDHI still qualifies as recommended regulatory heads BAPETEN Number 9 In 2011 on quality assurance (QA) or quality control (QC) of the CT Scan.                                                  Keywords: Compliance Test, CT number, Water Phantom, ROI, Tolerance Value.